Analysis and Simulation of Shifting-impact of Transmission System of Engineering Vehicle - Zou Hong; Duan Jianrui; Yao Jin (Jixie chuandong)
The evaluation indexes of vehicle shift quality,including the shifting-impact,the friction work and the shifting-time are given,combining with the ZL50 loader transmission system and the changes of the shift torque of the power shift clutch in the hydraulic control,several main factors of shift quality are summarized,the impact of the evaluation index is simulated and analyzed by using Matlab/Simulink. Finally,the improved control strategy is given through the experiment.